Strategi Penguatan Lulusan Edupreneurship Melalui Pemanfaatan E-commere: Studi Kasus di Universitas Al-Amien Prenduan Tahun 2024/2025 - Madona Agustin Sari; Izzat Amini (Lembaga Pengembangan Kinerja Dosen, 2026)
In the digital era, e-commerce has developed not only as a platform for buying and selling activities but also as a strategic medium for marketing and business development. University students theoretically possess strong potential to become edupreneurs because they are closely connected to technology and supported by higher education environments. Nevertheless, the reality at Al-Amien Prenduan University indicates that students tend to act more as consumers in e-commerce rather than as entrepreneurs. This condition creates a gap between theoretical expectations and practical implementation, raising questions regarding the effectiveness of e-commerce in encouraging students’ entrepreneurial spirit. This study examines strategies for strengthening Edupreneurship graduates through the optimization of e-commerce. The research specifically explores ways to maximize e-commerce in supporting the development of Edupreneurship graduate profiles and improving graduates’ competitiveness in entrepreneurship and employment sectors. A qualitative approach with a case study method was employed at Al-Amien Prenduan University. Data were collected through observation, interviews, and documentation involving female students of the Islamic Education Edupreneurship program who actively engage in entrepreneurial activities through e-commerce platforms. The findings reveal that optimizing e-commerce can be achieved through identifying students’ digital competencies and needs, as well as utilizing flexible technologies that support broader market access and global transactions. In addition, strategies such as enhancing digital marketing creativity, strengthening market research capabilities, and understanding consumer behavior significantly contribute to entrepreneurial development. The study concludes that e-commerce effectively fosters entrepreneurial attitudes, adaptability, and competitiveness among students in facing the challenges of the digital economy.